2020
DOI: 10.1016/j.ebiom.2020.102960
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, immunological and virological characterization of COVID-19 patients that test re-positive for SARS-CoV-2 by RT-PCR

Abstract: Background Some COVID-19 cases test positive again for SARS-CoV-2 RNA following negative test results and discharge, raising questions about the meaning of virus detection. Better characterization of re-positive cases is urgently needed. Methods Clinical data were obtained through Guangdong's COVID-19 surveillance network. Neutralization antibody titre was determined using microneutralization assays. Potential infectivity of clinical samples was evaluated by cell inocul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
116
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(122 citation statements)
references
References 17 publications
(28 reference statements)
3
116
3
Order By: Relevance
“…As an exception, a cohort study on paediatrics reported that seven patients out of 14 (50%) experienced recurrence [ 20 ]. Regardless of study type, based on 57 studies with available data (1019 patients), the first detection of recurrence of SARS-CoV-2 had been reported within a mean of 20 days, with a range of 1–140 days after meeting criteria for discharge [ 3 , 13 , 15–17 , 19–23 , 26–33 , 35–39 , 41–74 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As an exception, a cohort study on paediatrics reported that seven patients out of 14 (50%) experienced recurrence [ 20 ]. Regardless of study type, based on 57 studies with available data (1019 patients), the first detection of recurrence of SARS-CoV-2 had been reported within a mean of 20 days, with a range of 1–140 days after meeting criteria for discharge [ 3 , 13 , 15–17 , 19–23 , 26–33 , 35–39 , 41–74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Within the first admission, considering 1064 patients, the majority of re-positive cases ( n = 987; 92.7%) were asymptomatic or had mild to moderate symptoms [ 1 , 3 , 13 , 14 , 16 , 17 , 19 , 21–24 , 26–28 , 30–33 , 36–45 , 47 , 48 , 50–52 , 54 , 56 , 58 , 59 , 61 , 62 , 64–67 , 69–73 , 75 , 77 ], but some of them had severe or critical disease ( n = 77, 7.3%) [ 1 , 13 , 18 , 21 , 23 , 24 , 27 , 30 , 31 , 35 , 36 , 39 , 42 , 43 , 46 , 49 , 55 , 60 , 63 , 68 , 74 ]. To compare the severity of disease during the first and second courses of illness in re-positive patients, 57 studies including 858 re-positive patients, it was reported that the disease severity decreased or remained unchanged in 835 cases (97.3%) [ 13 , 15–20 , 23 , 24 , 26 , 28–31 , 33 , 36–48 , 50 , 52–54 , 58–61 , 65–68 , 70 , 71 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although bona fide re-infection of SARS-CoV-2 after recovery has been reported lately 15 , cohort-based studies with strict quarantine on subjects recovered from COVID-19 suggested "re-positive" cases were not caused by re-infection 16,17 . Furthermore, no replication-competent virus was isolated or spread from these PCR-positive patients 1-3, 5,6,12 . The cause for such prolonged and recurrent viral RNA production is unknown.…”
Section: Introductionmentioning
confidence: 97%
“…The specificity and sensitivity of RT-qPCR were 98.08% and 100.0%, respectively [ 74 ]. In addition, RT-PCR method has been used by many researchers to test SARS-COV-2 virus and has been widely used in clinical trials [ [75] , [76] , [77] ]. For example, Li et al developed a novel qRT-PCR method to detect SARS-COV-2 virus with a detection limit of 365.0 copies/mL.…”
Section: Detection Methodsmentioning
confidence: 99%